The use of Complementary and Alternative Medicine (CAM) among Italian children: A cross-sectional survey. (December 2019) - Stampini, Viviana; Bortoluzzi, Sara; Allara, Elias; Amadori, Roberta; Surico, Daniela; Prodam, Flavia; Barone-Adesi, Francesco; Faggiano, Fabrizio
Highlights: 48.3% of children in Novara has been treated with CAM at least once in life. 81.5% of pediatricians prescribes CAM, particularly herbal medicine and homeopathy, but only the 13, 6% of them have received a specific training. CAM are mostly used to treat pathologies of ear, nose and throat. Abstract: OBJECTIVE: To examine prevalence and modalities of CAM use in children living in Novara, a northern Italian city, and to estimate the prescription rate from paediatricians. METHOD: We administered a phone questionnaire to the parents of a sample of 147 children, asking questions about CAM use, children's health profile, parental socio-economic status, use modalities, effectiveness perceptions, and motivations. A parallel survey was conducted by e-mail by investigating family paediatricians attitudes about CAM. RESULTS: Among 147 children whose families responded to our survey 48.3% was treated with CAM at least once in life and 38, 1% during the previous year. Children treated with CAM were on average younger than those who were not. The types of CAM used were herbal medicine and homeopathy. Parents who choose CAM for their children were more skeptical about vaccinations. CAM were most frequently used to treat pathologies of ear, nose and throat. 85.9% of parents was willing to use CAM in future, 78.9% would pass to conventional medicine if CAM failed. Among paediatricians 81.5% prescribed CAM at least once, but only 13.6% received specific CAM training. CONCLUSION: The prevalence of children using CAM in Novara is high, in line with investigations conducted in Northern European countries. The distribution of pathologies treated with CAM, parental socio-economic status and general scepticism towards vaccination are consistent with the literature. Physicians should keep themselves up-to-date also about evidence-based CAM therapies and, most importantly, should have an open dialogue about CAM with their patients.